Immersive Learning Research from SVR Publications: A Re-conduction of the Systematic Mapping Study - Fernandes, Filipe; Castro, Diego; Werner, Cláudia (Journal on Interactive Systems, 2022)
Immersive Learning (iL) is known as a recent area of research that uses three-dimensional virtual environments and multi-sensory devices, also known as immersive technologies, to support the improvement of learning outcomes. This work aims to obtain evidence of theoretical and technological aspects of iL from the Symposium on Virtual and Augmented Reality (SVR) publications. A Systematic Literature Mapping protocol was developed and executed in order to select the primary studies to perform the analysis and data extraction. 76 primary studies helped to answer the research questions. A large part of the contributions by the SVR community are virtual environments that support education in the health area. In addition, some gaps and research opportunities were identified: virtual environments that serve audiences with special needs; development frameworks that consider pedagogical aspects; the use of biometric measures to support the validation of improved learning outcomes and more flexible tools that support educators in the development of immersive virtual environments that do not require specific knowledge in coding or 3D modeling.